2021
DOI: 10.1080/13603124.2020.1850869
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of leadership for learning beliefs among Flemish secondary school leaders

Abstract: Leadership for Learning (LFL) recently emerged as a comprehensive framework integrating aspects of theories thus far applied in school leadership research. LFL provides the principles for practice believed to effectively deal with the increasing complexity and expectations in education.Via semi-structured interviews this paper seeks to deepen our understanding of the leadership practices and beliefs among principals in Flemish secondary education and assess the occurrence of LFL in practice. Due to busy schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As this network only represents four percent of all Flemish secondary school leaders, PLCs comprising of otherwise affiliated school leaders might render deviating results. We do, nonetheless, only hypothesise slight, instead of considerable, deviations given recent studies on Flemish school leadership showed principals to face similar challenges (and obstacles) in exercising their jobs [3,96]. In this regard, researchers should continue to examine the conditions under which networked principal PLCs can render fruitful results from a distributed leadership point of view and the ways in which these can find an actual transfer to teachers' rooms and classroom floors.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 86%
See 2 more Smart Citations
“…As this network only represents four percent of all Flemish secondary school leaders, PLCs comprising of otherwise affiliated school leaders might render deviating results. We do, nonetheless, only hypothesise slight, instead of considerable, deviations given recent studies on Flemish school leadership showed principals to face similar challenges (and obstacles) in exercising their jobs [3,96]. In this regard, researchers should continue to examine the conditions under which networked principal PLCs can render fruitful results from a distributed leadership point of view and the ways in which these can find an actual transfer to teachers' rooms and classroom floors.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 86%
“…For, whereas a clear line of communication can aid members' perception that everyone agrees on a narrowly defined objective the group is to pursue, all other parts of group development are harder to come by as time to deliberately spend on those will always be scarce. We noticed that as our principals operate in a demanding environment [2,8] in which a multitude of small and ad hoc problems require a lot of their precious professional time [96], they were only able to meet at a relatively low frequency with fluctuating attendance rates. Exactly those frequent changes in group composition strongly hampered group development, definitely within the entirely unacquainted group: Members had to repeatedly introduce themselves, their school context and learning questions.…”
Section: Conditions For Succesful Principal Plcsmentioning
confidence: 99%
See 1 more Smart Citation